Algunos Problemas en Hematología Comparada - Jakowska, Sophie (Revista de Biología Tropical, 1959)
A historie and critical review is made of comparative hematology; its nomenclature is discussed, stressing the importance of the hematopoietic process in the production of analogous but not homologous types of cells in different vertebrate groups. Special discussion is made of the problems of pseudoerythro plastic anemia in Diemictylus viridescens and of enucleated red cells in cold blooded vertebrates in normal and abnormal circunmstances : the latter usuall y related to respiratory difficulties or abnormally high temperatures.